Scheduling in the university: mathematical methods and software - N. Samsonova (State University of Management, 2019)
Automating of scheduling in a university is an important issue. From a mathematical point of view, this is an integer programming challenge. The complexity of its solution is associated with a significant dimension of the problem being solved, a large number of restrictions, possible nonlinearity of the objective function, the complexity of the individual requirements formalization. There were attempts to apply the widest range of optimization methods to automate scheduling in university: linear programming methods, reducing the dimensionality reduction methods, clustering, agent modeling, genetic algorithm, the simplest brute-force plans. All these methods do not guarantee efficient plans obtainment in a reasonable time but many are able to find fairly good solutions. There are also technical difficulties associated with the needs of the large amounts of data processing. Organizational characteristics of specific universities also can become a significant problem with automation, which creates high requirements for portability and customization of the software product. Nevertheless, there is a number of programs that allow solving the scheduling automating problem, and some of this programs functions are considered in this article. All programs are also characterized by solving issues of documenting the processes associated with scheduling, including the ability to compile various types of schedules, the ability to export schedules into Word and Excel, automatic mailing etc. However, all this programs have a function of manual adjustment of the created schedule, which indirectly indicates the possibility of improving the applied algorithms.